Prawda o zmartwychwstaniu i życiu wiecznym w najmłodszych pismach natchnionych Starego Testamentu - Homerski, Józef (The Biblical Annals, 2017)
The following texts: Dan 12, 1-3; 2 Mac 7, 9.14 and Wisd 2, 23 and 3, 4 preach the doctrine about faith in the resurrection of good and bad people alike, and lead up to the truth about universal resurrection. Resurrection it a deed of God Creator and Salvator who gives eternal life to every man as a person. Resurrection to life is an award for present life in tune with God’s law. The resurrection of sinful people leads them to life in eternal humiliation. The Book of Wisdom speaks not only about immortality, e.g. eternal life in an intimate relationship with God, through which it takes on a sense of the reality being truly spiritual and supernatural.